The Effectiveness of a Cricket Programme for Engaging People with a Disability in Physical Activity in Fiji. Issue 2 (4th March 2018) - Beckman, Emma; Rossi, Tony; Hanrahan, Stephanie; Rynne, Steven; Dorovolomo, Jeremy
Abstract: Sport has been demonstrably linked to health particularly through community-based education and development programmes. However, research continues to identify low participation rates of people with a disability in sport. Programmes to address the participation of people with a disability in sport can be challenging, particularly in locations in the Pacific region. The primary aim of this project was to determine the activity levels of people with a disability during a cricket programme delivered in Fiji by Cricket Fiji with support from the International Cricket Council based in Melbourne Australia. A secondary aim was to investigate the relationship between levels of physical activity in the programme and self-esteem and indicators of general adaptive functioning. Results showed that means for self-description scales were high. Step count analysis showed a wide range of steps taken during the programme but similar steps between males and females. Correlations between self-description items and steps showed moderate relationships for self-esteem and confidence. This study showed that the programme was able to effectively provide physical activity opportunities for people with a disability and provides context to the development of longitudinal programmes that should aim to improve physical activity participation and health literacy in this population long term.